PKM Pembuatan Materi Video Interaktif untuk Staf Pengajar D-LLA Course menggunakan Aplikasi Powtoon - Agus Darmawan; Syamsiah Syamsiah; Halimatus’sadiah; Julizal Julizal (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Digitalization in education has encouraged the need to develop interactive and interesting learning media to increase student interest and understanding. Teaching staff at D-LLA Course, a tutoring institution, needs skills in using technology, one of which is making interactive videos. This article discusses the results of a training program held to improve teacher competency in using the Powtoon application to create interactive video learning materials. Through introductory methods, tutorials, direct practice and evaluation, this activity succeeded in improving teachers' skills in compiling digital learning content. Based on evaluations and feedback from participants, the majority felt that this interactive video learning method was more interesting for students and more effective in explaining the material. It is hoped that the results of this training can be implemented on an ongoing basis in the D-LLA Course to improve the quality of learning.